1983
DOI: 10.1007/978-3-642-68866-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics of Glucagon

Abstract: The object of this chapter is to describe the covalent chemistry of pancreatic glucagon to provide a background for subsequent chapters. Modifications of the primary structure are considered with respect to biologic activity, but not immunologic activity which is discussed in Chap. 9. Conformation and function are considered in Chap. 3. B. Isolation and PurificationGlucagon is effectively extracted from animal pancreas by any of the acidic ethanol methods commonly employed to extract insulin (e.g., SUTHERLAND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…In terms of cAMP generation in cultured hepatocytes, oxidized glucagon was found to be slightly less potent than glucagon by one group [12] and much less potent by another [23]. Another group found that the potency of oxidized glucagon in causing glycogenolysis was normal [3]. In our study, rather than oxidizing native glucagon oxidation, we synthesized Met sulfoxide de novo and found that its potency and power to be essentially normal.…”
Section: Discussionmentioning
confidence: 73%
“…In terms of cAMP generation in cultured hepatocytes, oxidized glucagon was found to be slightly less potent than glucagon by one group [12] and much less potent by another [23]. Another group found that the potency of oxidized glucagon in causing glycogenolysis was normal [3]. In our study, rather than oxidizing native glucagon oxidation, we synthesized Met sulfoxide de novo and found that its potency and power to be essentially normal.…”
Section: Discussionmentioning
confidence: 73%
“…Earlier studies of the structure-function relationships ofglucagon indicate that the amino terminus is involved in the signal transduction and biological potency of the peptide, whereas the carboxyl terminus is primarily responsible for recognition and binding to receptors (25). Hence, GLP-I-(1-37) may be an inactive precursor, which undergoes further processing to expose a new amino-terminal region that confers bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Glucagon, a 29 amino acid peptide hormone playing an important endogenous role in maintaining normal circulating glucose levels, is commercially available as a pharmaceutical preparation for the treatment of hypoglycemia and other clinical applications (11). Due to limitations in both chemical and physical stability of glucagon, the pharmaceutical product is supplied as a lyophilized powder that must be used immediately after reconstitution with its supplied aqueous diluent (12). Of particular concern is the propensity of glucagon to aggregate resulting in the formation of fibrils and gels; a process that can be stimulated by acidic pH, increased ionic strength, peptide concentration, agitation, and/or elevated temperatures (12,13).…”
Section: Introductionmentioning
confidence: 99%